Investigation of the Effect of “Dry” Immersion on the Optical Apparatus of the Eye - Gracheva, M. A.; Manko, O. M. (Human physiology, 2024)
The studies of astronauts’ vision show that after space flight various changes can occur in the visual system: flattening of the eyeball, optic disc edema, hyperopic refractive shift, and others. The mechanisms of those changes are being actively studied. Among model experiments simulating aggressive factors of space flight, experiments on modeling microgravity in conditions of “dry” immersion seem to be one of the most promising in terms of studying eye changes. The aim of the paper is to evaluate the prospects of using “dry” immersion as a model for studying intraocular changes in space flight conditions. The paper presents data on the evaluation of the eye condition of the test subjects after being in the immersion bath for 5 days (10 subjects) and 21 days (6 subjects). Refraction and dynamic accommodation were evaluated in all subjects using an Righton Speedy-i k-model autorefractometer with a dynamic accommodation assessment function. The refraction data showed a trend toward a positive refractive shift of 0.11 diopters on average for 5 days of immersion (confidence interval (–0.06)–(+0.28)) and 0.29 diopters (c.i. (–0.28)–(+0.86)); no statistical significance of the differences was confirmed, which may be due to the small number of subjects and the limited power of the statistical criterion. However, the trend requires further investigation. A significant individual variation was shown in the results of accommodation assessment. Preliminary data suggest that “dry” immersion may be a promising model for studying the effects of reduced gravity on the human visual system. Further studies are needed.